The Effect of Human Hair Fibers on the Behavior of Subgrade Clay Soil - Khushally, Yasser Al; Talib, Yosif Jamal; Nihad, Al-Zahraa Rashed; Hussein, Ehab Abaas (Al-Nahrain Journal for Engineering Sciences, 2025)
Soil reinforcement techniques have been successfully used to improve the shear properties of weak soils in recent years. To improve the utilization of waste resources and promote sustainable development of infrastructure amid rapid urbanization, one potential option for reinforcement materials is human hair fibers (HHF). Because it is a natural fiber, there are risks to human and environmental health associated with the improper disposal of human hair fiber, an occurring waste product that does not decompose completely. This fabric is abundant, has a high reusability rate, and is ideal for use as a reinforcement to address waste management issues and make the most of inefficient or unnecessary manufacturing websites for long-term sustainability. The CBR test was executed on several samples with diverse fiber possibilities to evaluate the engineering properties of the randomly placed HHF in clayey soil samples using fibers whose average length was 50 mm and whose diameter ranged from 60 to 80 microns and compared the outcomes to those of unreinforced soil. The soil sample was treated with different percentages of Human Hair fiber (0%, 0.75%, 1.5%, 1.75% and 2.25%). The results showed that the value of CBR of the soil sample decrease at 0.75% of HHF and then increased up to 2.25% of HHF.